PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) - Virnanda, Fariz Abditama; Armanu, Armanu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
In order to help companies reaching success, the employees need to work more, in this case by increasing Organizational Citizenship Behavior (OCB); the factors of which are workplace environment and work motivation. The objective of this research is to identify the effects of workplace environment and work motivation on the organizational citizenship behavior of the employees of the Directorate of Finance and Risk Management of PT Perusahaan Gas Negara Tbk. branch office of Jakarta. The samples of this explanatory research are 108 employees, selected using probability sampling method and simple random sampling technique. The data was harvested from questionnaires, that had been assessed using validity and reliability tests, followed by the classical assumption test. The results of the multiple linear regression performed in SPSS version 20 indicate that workplace environment and work motivation partially have positive effects on organizational citizenship behavior. This fact indicates that any increase in workplace environment and work motivation will also be followed by an increase in the organizational citizenship behavior of employees of the Directorate of Finance and Risk Management of PT Perusahaan Gas Negara Tbk. branch office of Jakarta.